Kesejahteraan Anak dan Perlindungan Hukum dalam Undang-undang Perlindungan Anak - Mu'ala, Abdulloh Afifil (Taruna Law: Journal of Law and Syariah, 2023)
This article discusses the importance of legal protection for children, emphasizing their rights as human beings and the need for a safe and nurturing environment for their growth and development. It highlights the significance of family as the primary caregiving institution for children but acknowledges that not all children receive adequate care and protection within their families. The article also explores the role of alternative caregiving institutions, such as Islamic boarding schools (pondok pesantren), in providing a supportive environment for children. It emphasizes the need for coordination and cooperation to ensure comprehensive child protection, not only from a legal perspective but also considering economic and social aspects. By examining the legal framework and practices related to child protection, the article aims to contribute to the improvement of child welfare in Indonesia, in line with national laws and international conventions on children's rights.